(untitled) (Damascus University Journal of agriculture sciences, 2021)
Multiple follicular stimulation with exogenous gonadotropins is a prerequisite to the efficient application of embryo transfer technology. While follicle stimulating hormone (FSH), and equine chorionic gonadotropin (eCG) were used frequently for superovulation in laboratory and farm animals, a little attention was paid for human menopausal gonadotropin (hMG). In this study, the effect of eCG was compared with that of hMG on ovarian response in immature Syrian female hamster to avoid interference by the stage of estrus. The females were equally assigned to one of two treatment groups each of 10 females, the first group was intraperitoneally (i.p) administered with 5 IU of eCG and the second group with 5 IU of hMG, respectively. As a control group, 10 cyclic females were permitted coitus with males of proven fertility and allowed to deliver pups. Ovaries were collected at 40-44 h after administration and all corpora lutea and follicles were counted. The results indicated that both eCG and hMG increased significantly (P< 0.05) follicular development on the ovaries (20.9 vs 29.2, respectively as compared with a main of 9.6 in the controls. However, the number of ovulations in hMG- group was fewer than eCG-group (1.7 vs. 20.9, respectively). It may be concluded that low levels of hMG are unsuitable for producing multiple embryos immature Syrian female hamster.